Blow up during warm-up: Introduction of a novel method to improve athletic performance - Thijssen, D. H. J.; Bailey, T. G.; Cable, T.; Hopman, M.; Atkinson, G.; Jones, H. (New Studies in Athletics, 2014)
ABSTRACT Short periods of transient blood flow restriction or ischaemia, known as 'ischaemic preconditioning' (IPC), are known to enhance both vasculature function and muscle function, which are important factors in sport performance. In this study, adapted from two papers published in the American Journal of Physiology and Medicine and Science in Sport and Exercise, the authors investigate the possibility that IPC could enhance performance in endurance running, and examine the potential underlying mechanisms related to lactate metabolism and changes in vascular function. After exposure to four cycles of five-minute bilateral cuff inflation on their upper thighs, 13 moderately training male participants performed running tests (to assess blood lactate accumulation), followed by a 5km time trial (to assess the impact of IPC on endurance running performance + vascular function). A significantly better performance was found in the mean 5km performance after the IPC condition. It was also found that IPC 1) attenuates blood lactate accumulation during submaximal exercise and 2) prevents impairment in vascular function that is typically associated with strenuous running exercise. The authors conclude that, with practical development, IPC may offer an inexpensive, easy applicable and non-invasive strategy to improve running exercise performance.